What fosters environmental engagement in China? Exploring the underlying pathways using the O-S-R-O-R model. Issue 1 (2nd January 2021) - Lu, Shuning
ABSTRACT: Building on the O-S-R-O-R framework, this study proposes the environmental communication mediation model and examines the formations of environmental engagement behavior in China. Analyzing data from the 2013 China General Social Survey ( N = 11, 438), this study shows that informational media use impacts environmental engagement both directly and indirectly through environmental discussion, environmental knowledge and external environmental efficacy. Findings also reveal a spillover effect between green purchasing behavior and environmental citizenship behavior. In addition, the results highlight the varied pathways from informational media use to the two types of environmental engagement across Eastern, Central, and Western China. The theoretical model developed in this study provides a coherent framework to understand the mechanisms of environmental engagement. It also enhances the external validity of the O-S-R-O-R model by extending it to the field of environmental communication. Lastly, the findings of the study underscore the role of contextual factors in shaping media use and its effects at the individual level.